Thermal inactivation of the corona virus (SARS-CoV-2) in air volumes - Schlott, André; Hutsch, Thomas; Sauer, Eileen; Wetschky, Jens; Hessel, Jana; Bailer, Susanne; Laubert, John; Lösch, Stefan (CLIMA 2022 conference, 2022)
To control the spread of viruses (e.g., SARS-CoV-2) and other pathogens in a pandemic situation, slowing down the rate of spread is an essential goal that can be achieved by interrupting transmission chains. According to the current state of knowledge, SARS-CoV-2 is mainly transmitted by droplet infection through virus-containing aerosol clouds in the air. These aerosol clouds are mainly produced by exhalation and can be reduced by wearing medical masks. In closed rooms, there is an increased probability of infection by aerosols. Countermeasures include various recently developed air cleaning technologies. Most of these technologies available on the market are based on filters with a limited lifetime to remove the virus load from the air or different sterilisation methods like UV irradiation. The air cleaning technology presented focuses on the thermal inactivation of viruses beyond their temperature sensitivity by heating the air. In the developed apparatus, the potentially germ-carrying ambient air is sucked in and conditioned in such a way that it is exposed to a certain temperature for a defined period of time. Before the inactivated / hygienised air is returned to the environment, it is cooled down to almost room temperature. The recovered heat remains in the system and is used to heat the intake air. The use and combination of different technologies enable the most efficient air disinfection possible. Four different experiments were conducted. After determining a base line, the air was solely passed through the pump, through the whole »Virus-Grill« pressure free and with an elevated pressure of 1.5 bar. In all experiments (except the baseline) the number of active viruses were reduced below the limit of detection.